Necessary and sufficient conditions for quasi-strongly regularity of Graph Product - Do, Tuan Minh; Vu, Hoa Dinh (Journal of Computer Science and Cybernetics, 2018)
A k-regular graph (k1) with n vertices is called a quasi-strongly regular graph with parameter λ (λ) if any two adjacent vertices have exactly λ neighbors in common. A graph product is a binary operation on graphs. In this paper we prove some necessary and sufficient conditions for Decartes Product, Tensor Product, Lexicographical product and Strong product to be quasi-strongly regular.